Hypoglycemia: awareness and challenges faced by patients with diabetes / Siti Nuraishah Hishammudin - Hishammudin, Siti Nuraishah (2014)
One of the most feared complications of diabetes treatment is hypoglycemia. Regrettably, the threat and incidence of hypoglycemia case is increased day by day in efforts to accomplish normal blood glucose level among diabetic patients. Incorrect administration of insulin or anti-diabetic medications, excessive physical activity, skipping a meal or decreased appetite may cause drops in blood glucose level. Low blood glucose level can have an effect on all the organs in the body, especially the brain (McConnell, 2007). There may be barriers in the management of this condition and this could potentially increase the risk on incidence and hence, affect patients' quality of life.